A thrombospondin structural repeat containing rhoptry protein from Plasmodium falciparum mediates erythrocyte invasion. (6th March 2013) - Siddiqui, Faiza Amber; Dhawan, Shikha; Singh, Shailja; Singh, Bijender; Gupta, Pankaj; Pandey, Alok; Mohmmed, Asif; Gaur, Deepak; Chitnis, Chetan E.
Summary: Host cell invasion by Plasmodium falciparum requires multiple molecular interactions between host receptors and parasite ligands. A family of parasite proteins, which contain the conserved thrombospondin structural repeat motif (TSR), has been implicated in receptor binding during invasion. In this study we have characterized the functional role of a TSR containing blood stage protein referred to as P. falciparum thrombospondin related apical merozoite protein (PfTRAMP). Both native and recombinant PfTRAMP bind untreated as well as neuraminidase, trypsin or chymotrypsin‐treated human erythrocytes. PfTRAMP is localized in the rhoptry bulb and is secreted during invasion. Adhesion of microneme protein EBA175 with its erythrocyte receptor glycophorin A provides the signal that triggers release of PfTRAMP from the rhoptries. Rabbit antibodies raised against PfTRAMP block erythrocyte invasion by P. falciparum suggesting that PfTRAMP plays an important functional role in invasion. Combination of antibodies against PfTRAMP with antibodies against microneme protein EBA175 provides an additive inhibitory effect against invasion. These observations suggest that targeting multiple conserved parasite ligands involved in different steps of invasion may provide an effective strategy forthe development of vaccines against blood stage malaria parasites.